Intestinal deletion of Claudin-7 enhances paracellular organic solute flux and initiates colonic inflammation in mice. Issue 10 (17th February 2015) - Tanaka, Hiroo; Takechi, Maki; Kiyonari, Hiroshi; Shioi, Go; Tamura, Atsushi; Tsukita, Sachiko
Abstract : Objective: To design novel anti-inflammation treatments, it is important to recognise two distinct steps of inflammation: initiation and acceleration. In IBDs, intestinal inflammation is reported to be accelerated by dysfunction in the epithelial paracellular barrier formed by tight junctions (TJs). However, it is unclear whether changes in paracellular barrier function initiate inflammation. Some of the intestinal claudin-family proteins, which form the paracellular barrier, show aberrant expression levels and localisations in IBDs. We aimed to elucidate the role of paracellular-barrier change in initiating colonic inflammation. Design: We generated intestine-specific conditional knockout mice of claudin-7 (Cldn7), one of the predominant intestinal claudins. Results: The intestine-specific Cldn7 deficiency caused colonic inflammation, even though TJ structures were still present due to other claudins. The paracellular flux (pFlux), determined by measuring the paracellular permeability across the colon epithelium, was enhanced by the Cldn7 deficiency for the small organic solute Lucifer Yellow (457 Da), but not for the larger organic solute FITC-Dextran (4400 Da). Consistent with these results, the intestine-specific claudin-7 deficiency enhanced the pFlux for N -formyl-l -methionyl-l -leucyl-l -phenylalanine (fMLP) (438 Da), a major bacterial product, to initiate colonic inflammation. Conclusions: These findings suggest that specific enhancement of the pFlux for small organic solutes across the claudin-based TJs initiates colonic inflammation.